An Interim Analysis of the Turkish Myeloma Registry Among the Patients Who Have Received up to Two Lines of Therapy - Sevindik, Omur Gokmen; Ozkurt, Zubeyde Nur; Boga, Can; Besisik, Sevgi Kalayoglu; Ipek, Yildiz; Geduk, Ayfer; Ozsan, Guner Hayri (Elsevier, 2021)
[Abstract Not Available]
63rd Annual Meeting and Exposition of the American-Society-of-Hematology (ASH) -- DEC 11-14, 2021 -- Atlanta, GA